POCKET: business proposal for subscription-based personal financial planning and advisory services in Malaysia - Shai, Gia Wei (2021)
POCKET is a private limited company that will be established in Malaysia. As a fintech, POCKET provides subscription-based personal financial planning and advisory services to Malaysia mass-market customers. By combining the best of high-tech and high touch of robo-advisor and human advisor, POCKET will reinvent the financial planning process in better efficiency and effectiveness, eventually transform personal financial planning and advisory services to be more accessible and affordable by Malaysians, especially for the low- to medium-income segment.